Novel Applications of Concentrated Growth Factors in Facial Rejuvenation and Plastic Surgery - Li, Guo; Wang, Hang (Facial Plastic Surgery, 2023)
Concentrated growth factor (CGF), which is a third-generation platelet concentrate product, exhibits good potential for repair and regeneration of soft and hard tissues, and has gradually attracted attention in the field of cosmetic plastic surgery. The purpose of this review is to summarize the application and research of CGF in the field of facial rejuvenation and plastic surgery. A comprehensive review of the literature about the applications of CGF in facial rejuvenation and plastic surgery was conducted in PubMed, Ovid MEDLINE, and Web of Science. According to the inclusion and exclusion criteria, a total of 22 articles were included in this review. In recent years, CGF has been applied in many aspects in the field of facial rejuvenation and plastic surgery, including skin photoaging, repairment of soft-tissue defects, rhinoplasty, hair loss, autologous fat transplantation, and scars. In addition, no significant adverse reactions have been reported so far. CGF is rich in high-concentration growth factors, which has great potential and application prospects in facial rejuvenation and plastic surgery. However, the applications of CGF still have some problems, such as the mechanism, time of decomposition, and long-term efficacy and safety, which are needed to be resolved in future.
Keywords: platelet concentrate products; concentrated growth factors; growth factors; facial rejuvenation; facial plastic surgery